Model Ketahanan Keuangan Syariah - Indrarini, Rachma; Samsuri, Andriani (Institut Agama Islam Negeri Madura, 2022)
The COVID-19 pandemic has had an adverse impact on the economy. Many people have lost their jobs but the necessities of life have increased. Society needs a model to make sharia financial resilience. This study aims to formulate a model of Islamic financial resilience, especially for Muslims by looking at three indicators are Islamic financial literacy, Islamic financial planning and Islamic financial inclusion. This research uses quantitative research with multiple linear regression. The result of this research is that Islamic financial literacy has no affect on sharia financial resilience. Islamic financial planning has not affect on sharia financial resilience. Islamic financial inclusion has affects on sharia financial resilience and together Islamic financial literacy, Islamic financial planning and Islamic financial inclusion has affect on sharia financial resilience